Techno-democracy: an alTernaTive To rule - Portillo, Nayades (Ingeniería Solidaria, 2012)
Electronic Government (eg) is a process of automation of local, regional or national governments. It is developed in different stages that vary depending on the resources, capacities, and priorities of the administration. From this perspective, the author reflects on the impact eg has had in the management of Community Action Committees (jac), and explains the importance of Information and Communications Technologies (ict) in this process, as they allow jacs to enter a reengineering process in order to correct the limitations of the decentralization of the services they provide. This article stems from the research project “Community Action Committees and Electronic Government” developed in 2009 at the Universidad Cooperativa de Colombia, Santa Marta branch.
Keywords: Electronic Government; Local Administrative Committees; techno-democracy